GRAMMATICAL ERROR ANALYSIS ON STUDENTS’ DESCRIPTIVE WRITING OF 4TH SEMESTER OF ENGLISH EDUCATION DEPARTMENT OF STAIN GAJAH PUTIH - Khoiriyah Shofiyah Tanjung (Jurnal As-Salam, 2019)
The purpose of this study is to analyze the grammar errors of students in writing descriptive paragraphs and explore the most dominant types of errors made by students. The population of this study is the fourth semester of English Education students at STAIN Gajah Putih Takengon which consist of two classes and 37 students. The author takes one class as a sample, namely TBI B. The sample is taken by Random Sampling because both classes have the same quality and are taught by the same lecturer. Data is collected from the student midterms answer sheet. The test results were analyzed using quantitative descriptive methods. The results showed that there were 92 mistakes made by students in writing descriptive paragraphs. 43.47% of these errors occurred in Disinformation, 26.08% were in addition, 21.73% errors in omission and 13.11% in misordering.